Threadbare: class and crime in urban Alaska - Kudenov, Mary, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2017)
Alaska's perch at the geographic corner of civilization isn't all wilderness and reality TV. There's a darker side too. Above the 49th parallel some of the nation's highest rates of alcoholism, suicide, and violent crime can be found. While it can easy to write off or even romanticize these statistics as the product of a lingering Wild West culture, talking with real Alaskans reveals a different story. Journalist Mary Kudenov set out to find the true stories behind this "end-of-the-road" culture. Through her essays, we meet Alaskans who live outside the common adventurer narrative: a recent graduate of a court-sponsored sobriety program, a long-timer in the Hiland Mountain Correctional Center for women, a slum-landlord's emancipated teenage daughter, and even a post-rampage spree killer. Her subjects struggle with poverty and middle-class aspirations, education and minimum wage work, God and psychology. The result is a raw and startling collection of direct, ground-level reporting that will leave you deeply moved.
Part One. Mercy. A History of Smoking -- Notes from a Baltic Avenue -- Open Holds -- Part Two. A Man of Fashion -- The Real Women of Hiland Mountain -- Part Three. Stronghold -- The Origin of Light -- Threadbare -- Trout Mostly.
Keywords: Alaska -- Social life and customs; Working class -- Alaska; Alaska -- Social conditions